2016
DOI: 10.1364/josaa.33.002459
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of power absorption response of periodic three-dimensional structures to partially coherent fields

Abstract: In many applications of absorbing structures it is important to understand their spatial response to incident fields, for example in thermal solar panels, bolometric imaging and controlling radiative heat transfer. In practice, the illuminating field often originates from thermal sources and is only spatially partially coherent when reaching the absorbing device. In this paper, we present a method to fully characterize the way a structure can absorb such partially coherent fields. The method is presented for a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The maximum achievable absorption is 87%, with a CD of approximately 70% at a wavelength ranging from 1.3 μm to 1.8 μm with high-contrast chiral reflective images. A bilayer design with remarkable selectivity for RCP and LCP wave absorption is proposed in [31]. Recently a plasmonic chiral metamaterial with T-shaped, I-shaped, and E-shaped structures stacked in a particular way has been used to build a bilayer for terahertz applications with high circular dichroism and considerable optical activity [32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…The maximum achievable absorption is 87%, with a CD of approximately 70% at a wavelength ranging from 1.3 μm to 1.8 μm with high-contrast chiral reflective images. A bilayer design with remarkable selectivity for RCP and LCP wave absorption is proposed in [31]. Recently a plasmonic chiral metamaterial with T-shaped, I-shaped, and E-shaped structures stacked in a particular way has been used to build a bilayer for terahertz applications with high circular dichroism and considerable optical activity [32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…He considered the absorption by a body illuminated by two deterministic phase-locked monochromatic sources located at two points r 1 , r 2 which generate an interference pattern in the absorbing body. To account for the effect of interferences on absorption, Rytov introduced a complex tensor quantity, the "mixed losses" [12][13][14][15], which can be measured experimentally [16,17]. Rytov showed that, for incandescent emitters at uniform tem-perature, the cross-spectral density tensor of the fields is directly proportional to the complex conjugate of the mixed losses [12].…”
mentioning
confidence: 99%